ESPECIFICAÇÕES DE PROJETO PARA MEDIÇÃO DE VELOCIDADE DE VENTO UTILIZANDO ANEMÔMETRO ULTRASÔNICO COM O MÉTODO DE DIFERENÇA DE FASE - Pinto, Mauro Sérgio Silva (2006)
The time of flight method for determining the wind speed using ultrasonic transducers is presented in this work. The techniques of phase difference and threshold detection for determining the time of flight are presented. A more detailed study of the phase difference technique is carried out in order to determine the design specifications using this method with respect to the noise sensitivity, dependence of the measurement range with the medium temperature and measurement resolution. A design specification example is presented in order to illustrate the proposed procedures.